High coral cover on a mesophotic, subtropical island platform at the limits of coral reef growth. (1st November 2016) - Linklater, Michelle; Carroll, Andrew G.; Hamylton, Sarah M.; Jordan, Alan R.; Brooke, Brendan P.; Nichol, Scott L.; Woodroffe, Colin D.
Abstract: Balls Pyramid is a volcanic monolith rising 552 m from the Tasman Sea, 24 km southeast of the Pacific Ocean's southernmost modern coral reef at Lord Howe Island. High resolution seabed mapping of the shelf surrounding Balls Pyramid has revealed an extensive submerged reef structure in 30–50 m water depth, covering an area of 87 km 2 . Benthic community composition analysis of high-resolution still images revealed abundant scleractinian corals on the submerged reef, extending to a maximum depth of 94 m. Scleractinian coral occurred predominantly in 30–40 m depth where it comprised 13.3% of benthic cover within this depth range. Average scleractinian coral cover for all transects was 6.7±12.2%, with the highest average transect cover of 19.4±14.3% and up to 84% cover recorded for an individual still image. The remaining substrate comprised mixed benthos with veneers of carbonate sand. Benthic data were shown to significantly relate to the underlying geomorphology. BVSTEP analyses identified depth and backscatter as the strongest correlating explanatory variables driving benthic community structure. The prevalence of scleractinian corals on the submerged reef features at Balls Pyramid, and the mesophotic depths to which these corals extend, demonstrates the important role of this subtropical island shelf as habitat for modern coral communities in the southwest Pacific Ocean. As Balls Pyramid is located beyond the known latitudinal limit of coral reef formation, these findings have important implications for potential coral reef range expansion and deep reef refugia under a changing climate. Highlights: Deep scleractinian corals were discovered around a remote, subtropical island shelf. Diverse tropical and temperate communities were characterised around the shelf. Scleractinian coral growth was observed down to depths of 94 m. Coral cover averaged 6.7% across all transects, with a maximum 84% per still image. Depth and geomorphology showed the strongest correlations to benthic distributions.